A low-emission strategy to recover lead compound products directly from spent lead-acid battery paste: Key issue of impurities removal. (10th February 2019) - Yu, Wenhao; Zhang, Peiyuan; Yang, Jiakuan; Li, Mingyang; Hu, Yuchen; Liang, Sha; Wang, Junxiong; Li, Suyuan; Xiao, Keke; Hou, Huijie; Hu, Jingping; Kumar, R. Vasant
Abstract: Hydrometallurgical route normally has lower energy consumption and less carbon dioxide emission than high-temperature smelting route. However, efficient removal of impurities is a common challenge for hydrometallurgical process. A facile recovery route of spent lead-acid battery pastes, including efficient desulfurization and pH-controlled acid leaching, is proposed. Effects of two typical desulfurizers (NaOH and Na2 CO3 ) on desulfurization efficiency and removals of major impurities (Ba and Fe elements) were comparatively investigated for the first time. NaOH was more effective than Na2 CO3 with a higher desulfurization efficiency of 99.3 wt% in 10 min. Approximately 26.2 wt% of BaSO4 in the raw spent lead paste was converted into BaCO3 in the Na2 CO3 desulfurization system, causing more Ba element entered into the acid leaching solution. The significant decrease of pH in the acid leaching solution caused a high concentration of Fe element impurity, which was efficiently removed by further pH adjustment. The optimal conditions were determined to be: a NaOH/PbSO4 molar ratio of 2.0 in the desulfurization step, a HNO3 /Pb molar ratio of 2.2 in the acid leaching step, and followed by adjusting the pH of the acid leaching solution to about 3.48. Up to 98.4 wt% of the Pb was recovered, while 99.8 wt% of Ba and 99.9 wt% of Fe element impurities were removed. The obtained low-impurity lead nitrate solution was further converted into high-purity PbCO3 and α-PbO products, providing a viable alternative for the recovery of the spent lead pastes. Graphical abstract: Highlights: NaOH exhibits higher desulfurization rate and efficiency than Na2 CO3 . Effect of desulfurizers on Ba impurity removal is studied for the first time. Removal of Fe impurity is dominantly controlled by pH in the acid leaching step. Removal efficiency of Ba and Fe can reach 99.8 and 99.9 wt%, respectively. High-purity PbCO3 and α-PbO products are recovered from the spent lead paste.